THE ROLE OF DIPLOMACY IN MAINTAINING PEACE: POLITICAL-DIPLOMATIC MEANS FOR THE PEACEFUL SETTLEMENT OF DISPUTES - Roxana-Mariana POPESCU (Challenges of the Knowledge Society, 2025)
Diplomacy plays an essential role in maintaining international peace, offering states – the main subjects of international law – a series of means for the peaceful settlement of disputes. This study analyzes the political-diplomatic means used in the management of disputes, such as negotiation, mediation, conciliation or good offices. The ways in which these instruments can be applied in practice and their effects on international relations are examined, by highlighting their limits.